Noa Industrias S. A.: un caso de éxito en el Parque Industrial de Villa El Salvador - Arbaiza Fermini, Lydia (2002)
The success story about the growth of a small home furniture manufacturing company located in the Industrial Park of Villa El Salvador is shown in this work. In order to ensure customer satisfaction and loyalty, models and designs are in continuous innovation.